Numerical study of Aeroacoustic sources generated from the wake behind the car - Nagawkar, Barlev (My University, 2016)
Due to new legislative and consumer demands Europe’s major vehicle manufactures (Original Equipment Manufacturer, OEMs) are forced to make big investments in the area of aeroacoustics. To measure a small noise contribution in wind tunnels is a challenge. Do to uncertainties of physical testing, the importance of using numerical methods for aeroacoustics has gone up. In this thesis an aeroacoustics study is performed on generic bodies with a focus on the wake. Three types of Ahmed bodies are used namely, the slant or fast back, the square or bus back and the notch or sedan back. The geometries being different in the rear will generate different wake structures and difference in noise levels obtained from these are analysed. An hybrid computational aeroacoustic method is adopted where first Large Eddy Simulations (LES) are done using AVL Fire to simulate the flow field. The sound propagation is then solved by using the Curle acoustic analogy.
Keywords: Strömningsmekanik och akustik; Hållbar utveckling; Transport; Fluid Mechanics and Acoustics; Sustainable Development; Transport